The value of translational biomarkers to phenotypic assays - Swinney, David C. (Frontiers in Pharmacology, 2014)
Phenotypic assays are tools essential for drug discovery. Phenotypic assays have different types of endpoints depending on the goals; 1) empirical endpoints for basic research to understand the underlying biology that will lead to identification of translation biomarkers, 2) empirical endpoints to identify undesired effects related to toxicity of drug candidates, and 3) knowledge-based endpoints (biomarkers) for drug discovery which ideally are translational biomarkers that will be used to identify new drug candidates and their corresponding molecular mechanisms of action. The value of phenotypic assays is increased through effective alignment of phenotypic assay endpoints with the objectives of the relevant stage in the drug discovery and development cycle.